Rio 2016 : Olympic myths, hard realities /: Olympic myths, hard realities. ([2017]) - Barbassa, Juliana; Boykoff, Jules; Chade, Jamil; Essex, Stephen; Sanchez, Renata Latuf de Oliveira; Williamson, Theresa
No abstract available